A New Type of Donor–Acceptor Cyclopropane Reactivity: The Generation of Formal 1, 2‐ and 1, 4‐Dipoles1. (19th February 2014) - Novikov, Roman A.; Tarasova, Anna V.; Korolev, Victor A.; Timofeev, Vladimir P.; Tomilov, Yury V.
Abstract A new type of donor–acceptor cyclopropane reactivity has been discovered. On treatment with anhydrous GaCl3, they react as sources of even‐numbered 1, 2‐ and 1, 4‐dipoles instead of the classical odd‐numbered 1, 3‐dipoles due to migration of positive charge from the benzyl center. This type of reactivity has been demonstrated for new reactions, namely, cyclodimerizations of donor–acceptor cyclopropanes that occur as [2+2]‐, [3+2]‐, [4+2]‐, [5+2]‐, [4+3]‐, and [5+4]‐annulations. The [4+2]‐annulation of 2‐arylcyclopropane‐1, 1‐dicarboxylates to give polysubstituted 2‐aryltetralins has been developed in a preparative version that provides exceedingly high regio‐ and diastereoselectivity and high yields. The strategy for selective hetero‐combination of donor–acceptor cyclopropanes was also been developed. The mechanisms of the discovered reactions involving the formation of a comparatively stable 1, 2‐ylide intermediate have been studied.